1997
DOI: 10.2190/df5n-hgfb-mvpk-u34d
|View full text |Cite
|
Sign up to set email alerts
|

Preferences in Symmetries and Symmetries in Drawings: Asymmetries between Ages and Sexes

Abstract: Visual structure in art has been studied by Amheim (1) and more recently by Leyton (2) who suggests that an analysis of symmetrical structure is fundamental to the understanding of visual structure. 1bree experiments revealed age and sex differences in symmetry preferences with dot patterns and productions in drawings by children and adults. Asymmetrical patterns were less preferred and seen as less symmetrical with age, while patterns with multiple symmetries [3] showed the opposite effects. Increasingly comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…They found that the productions created and those selected were influenced by gender stereotypical content, further showing a relationship between preference and production. Furthermore, symmetry has also been found to impact art production with use of symmetry in creations differing dependent on gender and age, however here it has been shown that there tends to be disparities between the types of symmetry preferred and those found in productions (Humphrey, 1997;Washburn & Humphrey, 2001). So, research…”
Section: Aesthetic Preference and Art Productionmentioning
confidence: 68%
“…They found that the productions created and those selected were influenced by gender stereotypical content, further showing a relationship between preference and production. Furthermore, symmetry has also been found to impact art production with use of symmetry in creations differing dependent on gender and age, however here it has been shown that there tends to be disparities between the types of symmetry preferred and those found in productions (Humphrey, 1997;Washburn & Humphrey, 2001). So, research…”
Section: Aesthetic Preference and Art Productionmentioning
confidence: 68%
“…It is possible that there are sex differences in preference for specific symmetries in relation to human judgments of visual art and abstract patterns (see Bernard, 1972;Humphrey, 1997;Johnson & Knapp, 1963). It is also possible that male and female aesthetic judgments for symmetry are based on a difference in perceived complexity.…”
Section: Discussionmentioning
confidence: 99%
“…This objectivist view inspired many psychological attempts to identify the critical contributors to beauty. Among the identified features were balance and proportion (Arnheim, 1974; Birkhoff, 1933;Fechner, 1876;Gombrich, 1995), symmetry (Arnheim, 1974; Birkhoff, 1933;Gombrich, 1984;Humphrey, 1997), informational content and complexity (Berlyne, 1971(Berlyne, , 1974Eysenck, 1941;Garner, 1974), as well as contrast and clarity (Gombrich, 1984(Gombrich, , 1995 St. Thomas of Aquinas, see Maritain, 1966;Solso, 1997). The objectivist view of beauty was so dominant in the 16th century that artists introduced pattern books, offering pictorial elements that artists could copy and combine with each other to create beauty (see Gombrich, 1995).…”
mentioning
confidence: 99%